Water Footprint and its relationship with family income: a study applied to Brazil - Barbosa, Alan; Branchi, Bruna Angela; Ferreira, Denise Helena Lombardo; Guedes, Walef Pena (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The urbanization process, accompanied by significant population growth, has promoted new consumption patterns that put pressure on natural resources. Faced with the challenges arising from unsustainable consumption, Sustainable Development Goal 12 of the 2030 Agenda seeks to promote sustainable methods of production and consumption, as well as the conscious use of natural resources. In this sense, this study aims to contribute to the debate on the relationship between the dietary patterns of the Brazilian population and family income by calculating the environmental indicator Water Footprint. To meet this objective, an appl0069ed research with a quantitative approach was carried out based on a bibliographical review carried out in the SCOPUS and Web of Science databases, from 2012 to May 2023. In addition, microdata from the latest Brazilian Institute of Geography and Statistics Household Budget Survey were employed, supported by the application of the multivariate statistical technique of Factorial Analysis. As a result, six main factors that characterize the main Brazilian dietary profiles were identified. The results confirmed that diets rich in animal protein tend to have a higher Water Footprint, the same as those found in the literature review. A strong correlation was also found between income and meat consumption, with higher income households consuming larger amounts of animal protein and, therefore, having a larger water footprint compared to those of lower per capita income households. The results prove the need to promote awareness about the environmental consequences of consumption and the importance of promoting healthy and sustainable eating habits.